A Phylogenomic Analysis of the Bacterial Phylum Fibrobacteres - Abdul Rahman, Nurdyana; Parks, Donovan H.; Vanwonterghem, Inka; Morrison, Mark; Tyson, Gene W.; Hugenholtz, Philip (Frontiers in Microbiology, 2016)
The Fibrobacteres has been recognized as a bacterial phylum for over a decade, but little is known about the group beyond its environmental distribution, and characterization of its sole cultured representative genus, Fibrobacter, after which the phylum was named. Based on these incomplete data, it is thought that cellulose hydrolysis, anaerobic metabolism, and lack of motility are unifying features of the phylum. There are also contradicting views as to whether an uncultured sister lineage, candidate phylum TG3, should be included in the Fibrobacteres. Recently, chitin-degrading cultured representatives of TG3 were obtained isolated from a hypersaline soda lake, and the genome of one species, Chitinivibrio alkaliphilus, sequenced and described in detail. Here, we performed a comparative analysis of Fibrobacter succinogenes, C. alkaliphilus and eight near or substantially complete Fibrobacteres/TG3 genomes of environmental populations recovered from termite gut, anaerobic digester, and sheep rumen metagenomes. We propose that TG3 should be amalgamated with the Fibrobacteres phylum based on robust monophyly of the two lineages and shared character traits. Polymer hydrolysis, using a distinctive set of glycoside hydrolases and binding domains, appears to be a prominent feature of members of the Fibrobacteres. Not all members of this phylum are strictly anaerobic as some termite gut Fibrobacteres have respiratory chains adapted to the microaerophilic conditions found in this habitat. Contrary to expectations, motility is is predicted to be an ancestral and common trait in this phylum and has only recently been lost in F. succinogenes and its relatives based on phylogenetic distribution of flagellar genes. Our findings extend current understanding of the Fibrobacteres and provide an improved basis for further investigation of this phylum.